The difference between Communicative Language Teaching and Audio-Lingual method - Alieva Shahlo Avazovna (Euro Asian Journal Publishing, 2024)
In this article, we explore the main differences between communicative language teaching and the audio-lingual method, highlighting their distinctive features and implications for language learners and teachers. By gaining a deeper understanding of these two methodologies, language teachers can make informed decisions about which approach best suits their students' learning needs and goals
Keywords: Language; reading methodology; audio-lingual method